Rancang Bangun Pendeteksi Kertas Struk pada Mesin Anjungan Tunai Mandiri Berbasis Mikrokontroler - Fattah, Muhammad Najihurrahman; Faisal, Faisal; Saputra, Wahyuddin (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2023)
Proof of transaction printed by an Anjungan Tunai Mandiri (ATM) generally produces printed electronic information about the amount of money, account for the transaction, location, and transaction time. Article 5 paragraph (1) of Law no.11 of 2008 concerning electronic information and transactions (